2014
DOI: 10.1089/fpd.2014.1803
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Salmonella on Turkey Breast Cutlets by Plant-Derived Compounds

Abstract: The foodborne illnesses associated with poultry meat due to Salmonella are a major concern in the United States. In this study, the antimicrobial efficacy of carvacrol, eugenol, thyme essential oil, and trans-cinnamaldehyde was determined against different Salmonella serotypes in vitro and on turkey breast cutlets. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of antimicrobial agents were determined using a microdilution colorimetric assay. Carvacrol was the most effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…The antimicrobial activity of carvacrol against S. Typhimurium ATCC 14028 was evaluated in vitro and MIC and MBC values were 312 µg mL -1 . Similar results were obtained by other studies using carvacrol against S. Typhimurium and other serotypes (Soni et al, 2013;Nair et al, 2014). MIC and MBC values ranging from 64 to 512 µg mL -1 were obtained by Miladi et al (2016) in S. Typhimurium and S. Enteritidis.…”
Section: Antimicrobial Activity Of Carvacrol Against Salmonella Typhisupporting
confidence: 89%
See 1 more Smart Citation
“…The antimicrobial activity of carvacrol against S. Typhimurium ATCC 14028 was evaluated in vitro and MIC and MBC values were 312 µg mL -1 . Similar results were obtained by other studies using carvacrol against S. Typhimurium and other serotypes (Soni et al, 2013;Nair et al, 2014). MIC and MBC values ranging from 64 to 512 µg mL -1 were obtained by Miladi et al (2016) in S. Typhimurium and S. Enteritidis.…”
Section: Antimicrobial Activity Of Carvacrol Against Salmonella Typhisupporting
confidence: 89%
“…In an attempt to find effective alternatives to control bacteria, studies have revealed the antibacterial (Burt, 2004;Luz et al, 2012;Chauhan, Kang, 2014;Nair et al, 2014) and antibiofilm activity of essential oils and their components (Bersan et al, 2014;Piovezan et al, 2014). Carvacrol is an important component of the essential oil of Origanum vulgari, and is present in the essential oils such as Thymus vulgaris (Lambert et al, 2001;Burt, 2004) and Satureja bachtiarica (Falsafi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…inch reductions of S. Heidelberg with 0.5 and 1.0% PEO, respectively at 4°C. It is comparable to the reduction achieved during post chill dip treatment using other synthetic antimicrobial agents or other EOs ( Nagel et al, 2013 ; Nair et al, 2014 , 2015 ). For example, 40 or 400 ppm chlorine and 1000 or 5000 ppm lysozyme resulted in less than 1 log 10 CFU/ml reduction of S. Typhimurium on broiler carcass when used as post-chill dip treatment for 20 s ( Nagel et al, 2013 ).…”
Section: Resultssupporting
confidence: 65%
“…Recently, there is a tremendous interest in using natural antimicrobials as an alternative to synthetic chemicals against pathogens during food production ( Burt, 2004 ; Lanciotti et al, 2004 ; Amalaradjou et al, 2010 ; Kollanoor Johny et al, 2010 ; Nair et al, 2015 ; Surendran Nair et al, 2016 ; Surendran-Nair et al, 2016 ). Among the emerging and widely researched alternatives, essential oils (EO) or their components are reported effective against foodborne pathogens such as Salmonella, Campylobacter , and Escherichia coli O157 in vitro and in vivo ( Kollanoor Johny et al, 2008 ; Amalaradjou et al, 2010 ; Kollanoor-Johny et al, 2012a , b ; Nair et al, 2014 , 2015 ). The United States Food and Drug Administration (USFDA) has approved the use of selected EOs in food matrices ( FDA, 2016 ) and therefore, their efficacy could be evaluated as safe and natural alternatives in commercial and organic poultry production systems ( GPO, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol (1% to 5%) treatment significantly reduces the reproduction of the S. heidelberg , S. enteritidis , and S. typhimurium on turkey breast cutlets, and this reduction is concentration‐dependent (Nair, Nannapaneni, Kiess, Schilling, & Sharma, ). Experiments in vivo show that eugenol (1.2 to 1.8 mM) significantly reduces the adhesion and invasion ability of S. enteritidis in chicken oviduct epithelial cells and survival ability in macrophages.…”
Section: The Antibacterial Actions and Mechanisms Of Clove Oil And Eumentioning
confidence: 99%